THE ABILITY OF THE FIRST YEAR STUDENTS OF MTS AL-USWAH PEKANBARU IN READING POETRY - Wahyuningsih, Umi Wahyuningsih; Razak, Abdul Razak; Burhanudin, Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research was intended to find out the ability of the first year students of Al-Uswah Pekanbaru. in reading poetry. The problem in this research is how the student’s ability in reading poetry consists of the aspects of vocal precision, intonation, and appreciation (expression). The method used in this research is descriptive quantitative with the sample were 44 students of the first year of MTs Al-Uswah Pekanbaru. The data was collected by provide a test reading text of the poem to the sample, and then provide an assessment in accordance with the assessment criteria that have been established, then look for the percentage, mean, two different tests, standard deviation, and standard deviation for each aspect combined assessed and a recapitulation result of data analysis. The research finding showed that (1) the ability to read poetry in aspects of vocal accuracy category with the average being 60.99, equivalent to 76.24 per cent (2) the ability to read poetry in intonation aspect being categorized with the average of 47.26, equivalent to 78 , 77 percent (3) the ability to read poetry in the aspect of appreciation (expression) low category with a mean of 41.22, equivalent to 68.71 percent. Overall, it can be concluded that the ability of the first year students of Al-Uswah Pekanbaru. in reading poetry is categorized with average 143.59 (for two poems), equivalent to 71.80 percent. Keywords: The Reading Ability Poetry